Phosphorescence of Carbon Nanodots – The Phenomena and the Applications - Aapasthamba Govindasamy; Indra Neel Pulidindi (International Journal of Photochemistry and Photochemical Research, 2026)
Photoluminescence has emerged as a fundamental phenomenon in modern biomedical science, enabling advanced diagnostic, therapeutic, and theranostic applications through light–matter interactions at the nanoscale. The ability of photoluminescent materials to absorb electromagnetic radiation and emit light at distinct wavelengths has been widely exploited in bioimaging, biosensing, drug delivery tracking, and photodynamic therapy. Among various photoluminescent nanomaterials, carbon nanodots have attracted significant attention due to their strong emission intensity, tunable fluorescence, excellent biocompatibility, and versatile surface chemistry. These properties make them highly suitable for integration into biomedical systems, where they enhance cellular interactions, facilitate reactive oxygen species generation, and enable targeted molecular signaling pathways. This review highlights the biomedical applications of photoluminescence with a particular focus on the mechanisms underlying biological interactions and the synergistic effects achieved through the incorporation of carbon nanodots. The discussion also covers recent global research developments and mechanistic insights that demonstrate how photoluminescent systems contribute to advancements in nanomedicine and therapeutic technologies. Furthermore, recent progress in the field has emphasized the importance of surface functionalization and doping strategies to precisely control emission characteristics and improve targeting efficiency in complex biological environments. The incorporation of heteroatoms and the development of hybrid nanostructures have significantly broadened the functional capabilities of carbon nanodots, enabling multiplexed imaging and stimuli-responsive behavior. Their inherent low toxicity, high stability under physiological conditions, and adaptability further support their potential for long-term biomedical applications. Emerging studies also underscore their growing role in precision medicine, where controlled photoluminescent responses enable real-time monitoring of disease progression, treatment efficacy, and therapeutic outcomes, paving the way for more personalized and effective healthcare solutions.
Keywords: Nanomedicine; biomedical imaging; carbon nanodots; photodynamic therapy; photoluminescence; theranostic